2018
DOI: 10.1111/codi.14249
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of parastomal hernia: a position statement on behalf of the Association of Coloproctology of Great Britain and Ireland

Abstract: There is a lack of high quality evidence for many domains in the prevention and treatment of PSH but the results of several studies are awaited. WHAT DOES THIS PAPER ADD TO THE LITERATURE?: Parastomal hernias are a common and debilitating condition following stoma formation. This position statement from ACPGBI details the current evidence base and ongoing research for the prevention, diagnosis and management of parastomal hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 101 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Currently there is a lack of high-quality evidence to guide treatment decisions. Surgeons do not know the best way to repair a PSH, nor do they know whether watchful waiting is safe or whether it can result in more complications [2]. Additionally, recurrence risks from PSH repair are high [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is a lack of high-quality evidence to guide treatment decisions. Surgeons do not know the best way to repair a PSH, nor do they know whether watchful waiting is safe or whether it can result in more complications [2]. Additionally, recurrence risks from PSH repair are high [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Given the risks of further surgery and high risk of recurrence after repair, it is important that people with parastomal bulging are given effective support, help and guidance to self-manage parastomal bulging without surgical intervention. Current guidelines only offer surgery as an option for parastomal bulging treatment and offer advice on prevention [ 13 ]. Alternative self-management options are not part of current advice or guidelines in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 24% of patients with an ostomy remain asymptomatic in the long term [5]. Subsequently, the Association of Coloproctology of Great Britain and Ireland identified that the prevention and treatment of PSHs are the second most important non-cancer-related issues due to high recurrence rates after hernia repair [6]. Although prophylactic mesh for PSH prevention has been advocated [7][8][9] a recent randomized controlled trial has shown that reinforcing meshes to prevent PSH formation cannot be recommended [10].…”
Section: Introductionmentioning
confidence: 99%